2016
DOI: 10.1038/nn.4417
|View full text |Cite
|
Sign up to set email alerts
|

Organization of long-range inputs and outputs of frontal cortex for top-down control

Abstract: Long-range projections from the frontal cortex are known to modulate sensory processing in multiple modalities. Although the mouse has become an increasingly important animal model for studying the circuit basis of behavior, the functional organization of its frontal cortical long-range connectivity remains poorly characterized. Here we used virus-assisted circuit mapping to identify the brain networks for top-down modulation of visual, somatosensory, and auditory processing. The visual cortex is reciprocally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
189
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(236 citation statements)
references
References 53 publications
30
189
0
Order By: Relevance
“…It has been suggested that rostral M2 receives more somatic sensorimotor inputs, whereas caudal M2 receives more sensory inputs [10,13]. There may also be regional differences: unlike Cg1 which primarily receives afferents from visual areas, M2 has auditory inputs in addition to visual afferents and may therefore be multi-modal [14]. …”
Section: Afferent Connections From Diverse Cortical and Thalamic Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that rostral M2 receives more somatic sensorimotor inputs, whereas caudal M2 receives more sensory inputs [10,13]. There may also be regional differences: unlike Cg1 which primarily receives afferents from visual areas, M2 has auditory inputs in addition to visual afferents and may therefore be multi-modal [14]. …”
Section: Afferent Connections From Diverse Cortical and Thalamic Sourcesmentioning
confidence: 99%
“…Regions targeted by prelimbic and infralimbic cortices, but not M2, include ventral striatum, periaqueductal grey, septum, ventral tegmental area, and a few others [18]. Depending on the efferent target, projection neurons in mPFC reside in different cortical layers [18], and can have distinct long-range axonal collaterals [14]. …”
Section: Efferent Connections To Distinct Targets For Action Controlmentioning
confidence: 99%
“…Previous work has demonstrated that rodent cingulate cortex has reciprocal connections with the visual area and projects to motor areas (64,65). In addition, visual stimulation can elicit evoked responses in the cingulate cortex (66), and direct electrical stimulation of cingulate cortex can elicit movement (67)(68)(69).…”
Section: Monocular Visual Deprivation Induces Intranetwork Change In mentioning
confidence: 99%
“…Identified candidate top-down circuits arising from frontal cortices include direct inputs to posterior sensory cortices, thalamus, and claustrum (Miller and Buschman, 2013; Zhang et al, 2014; Mathur, 2014). Given that prefrontal cortex neurons can encode task performance differentially based on projection target (Otis et al, 2017), it is critical to determine which signals are being propagated to claustrum, for instance, and how these signals (Zhang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…However, it is unknown whether claustrum mediates top-down or bottom-up information flow (Mathur, 2014), sits atop the information processing hierarchy to bind sensory information for conscious perception (Crick and Koch, 2005), or exists solely as a satellite processer for cortices (Olson and Graybiel, 1980). Based on recent work showing that the rat claustrum receives a dense innervation from the anterior cingulate cortex (ACC; White et al, 2017), an area implicated in top-down attention (Zhang et al, 2014, 2016), we hypothesize that the claustrum is positioned to receive top-down input for cognitive control (Mathur, 2014). Testing this, we found that ACC input to the mouse claustrum encodes an anticipatory top-down signal that is proportional to task load and required for optimal performance accuracy.…”
Section: Introductionmentioning
confidence: 99%